Pengaruh Teknik Pembelajaran Role Playing dalam Meningkatkan Keterampilan Berbicara Siswa Kelas VII SMPN 27 Satu Atap Lappawarue Kecamatan Mallawa Kabupaten Maros - Umraira Umraira; Rosmini Madeamin; Fajrul Khaer (Jurnal Pendidikan dan Sastra Inggris, 2025)
The speaking skills of seventh-grade students at SMPN 27 Satu Atap Lappawarue are still considered low.This is caused by the students' low self-confidence in speaking in public and the use of teaching methods that do not encourage active participation.This study aims to determine the extent of the influence of the Role Playing learning technique in improving students' speaking skills in the Indonesian language subject. The type of this research is Pre-Experiment.The research design is a Pretest-Posttest Design, which is an experiment that involves only one class as the experimental class without a comparison class (control class).The subjects used in this study were 12 students. The results of the descriptive statistical analysis show that the use of the Role Playing learning technique has a positive impact on the improvement of students' speaking skills.The average speaking skill scores of the students increased from 44 during the pretest to 79 after the posttest.This shows that after the Role Playing technique was applied, the students' speaking skills experienced a significant improvement compared to before the technique was implemented.The results of the inferential statistical analysis using the t-test formula show that the calculated t-value obtained is 9.358 with a frequency (df) = 12 – 1 = 11.At a significance level of α = 0.05, the t-table value obtained is 2.200.Thus, t calculated > t table, so the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted.This proves that there is a significant influence of the Role Playing technique on the speaking skills of seventh-grade students at SMPN 27 Satu Atap Lappawarue, Mallawa District, Maros Regency.